Ökumene - Rück- und Vorblick: zum Beitrag Yves-Marie Congars O.P. : 13.4.1904 - 22.6.1995 - Neufeld, Karl H. (Zeitschrift für katholische Theologie, 2004)
Yves-Marie Congar was born, like Rahner and Lonergan, 100 years ago. He became the pioneer of Catholic ecumenism in the 20th century. This article wants to contribute to the recognition his theological work deserves particularly in the German speaking world and calls to mind some of his suggestions that may enrich even today's ecumenical dialogues.